Articulating What Infants Attune to in Native Speech. Issue 4 (1st October 2016) - Best, Catherine T.; Goldstein, Louis M.; Nam, Hosung; Tyler, Michael D.
ABSTRACT: To become language users, infants must embrace the integrality of speech perception and production. That they do so, and quite rapidly, is implied by the native-language attunement they achieve in each domain by 6–12 months. Yet research has most often addressed one or the other domain, rarely how they interrelate. Moreover, mainstream assumptions that perception relies on acoustic patterns whereas production involves motor patterns entail that the infant would have to translate incommensurable information to grasp the perception–production relationship. We posit the more parsimonious view that both domains depend on commensurate articulatory information. Our proposed framework combines principles of the Perceptual Assimilation Model (PAM) and Articulatory Phonology (AP). According to PAM, infants attune to articulatory information in native speech and detect similarities of nonnative phones to native articulatory patterns. The AP premise that gestures of the speech organs are the basic elements of phonology offers articulatory similarity metrics while satisfying the requirement that phonological information be discrete and contrastive: (a) distinct articulatory organs produce vocal tract constrictions and (b) phonological contrasts recruit different articulators and/or constrictions of a given articulator that differ in degree or location. Various lines of research suggest young children perceive articulatory information, which guides their productions: discrimination of between- versus within-organ contrasts, simulations of attunement to language-specific articulatory distributions, multimodal speech perception, oral/vocal imitation, and perceptual effects of articulator activation or suppression. We conclude that articulatory gesture information serves as the foundation for developmental integrality of speech perception and production.